News media credibility of the internet and television - Mehrabi, Davood; Abu Hassan, Musa; Shahkat Ali, Muhamad Sham (EuroJournals Publishing, Inc., 2009)
In this study, a survey design was used to determine the factors influences the perception of media credibility to decipher how respondents perceive the Internet and television in terms of credibility for news information. A survey with 270 non-academic professional staff was conducted to determine the factors that influence their perception towards media credibility. The systematic sampling method was used to select for inclusion in the sample. The results of the study revealed that television is more credible than Internet to convey news. This study also explored a positive and significant relationship between issue salience, media reliance, and media usage with perception of the Internet and television credibility.